The role of sociodemographic risk and maternal behavior in the prediction of infant attachment disorganization. Issue 6 (1st November 2016) - Gedaly, Lindsey R.; Leerkes, Esther M.
ABSTRACT: Predictors of infant attachment disorganization were examined among 203 primiparous mothers (52% European American, 48% African American) and their infants (104 female). The Strange Situation Procedure was administered at one year. Global maternal insensitivity and overtly negative maternal behavior were observed during distress-eliciting tasks when infants were six months and one year old. Mothers reported on their demographics to yield a measure of sociodemographic risk (i.e., age, education, income-to-needs). Overtly negative maternal behavior was positively associated with the infant attachment disorganization rating scale score, but did not predict being classified as disorganized. Global maternal insensitivity was associated with higher attachment disorganization, both the rating and the classification, when sociodemographic risk was high but not when sociodemographic risk was low. The pattern of results did not vary by maternal race. The results provide some support for the view that negative maternal behavior and the combination of sociodemographic risk and global maternal insensitivity play a role in the development of infant attachment disorganization.